2019
DOI: 10.4236/ojvm.2019.95005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Bovine Tuberculosis by Comparative Intradermal Tuberculin Test, Interferon Gamma Assay and <i>esxB</i> (CFP-10) PCR in Blood and Lymph Node Aspirates

Abstract: Bovine tuberculosis (TB) is a chronic debilitating disease of huge economic importance due to loss in production, morbidity and mortality, and has a potential zoonotic threat. TB is endemic in India and has a worldwide prevalence, therefore, needing early diagnostic technique for the eradication of TB globally. Currently, compared to the eradication programme of TB in Medical sector, Veterinary sector is lagging behind though TB is one of the major zoonotic diseases prevalent in dairy animals and wildlife in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In 1882, Koch discovered the tubercle bacillus of Mycobacterium tuberculosis ( Mtb ), the causative agent of human TB [ 2 ], whilst Smith in 1898, identified M. bovis as a different species from Mtb [ 3 ]. Bovine TB has a marked economic importance because of loss in productivity, morbidity, and mortality, in addition to the potential zoonotic threat [ 4 ]. The surveillance costs also have immense economic importance.…”
Section: History Of Bovine Tuberculosis (Btb)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 1882, Koch discovered the tubercle bacillus of Mycobacterium tuberculosis ( Mtb ), the causative agent of human TB [ 2 ], whilst Smith in 1898, identified M. bovis as a different species from Mtb [ 3 ]. Bovine TB has a marked economic importance because of loss in productivity, morbidity, and mortality, in addition to the potential zoonotic threat [ 4 ]. The surveillance costs also have immense economic importance.…”
Section: History Of Bovine Tuberculosis (Btb)mentioning
confidence: 99%
“…Besides tissue samples, many PCR assays had been performed on blood and milk samples such as the Mataragka et al study, which illustrated that PCR can be used as an early and sensitive indicator method to detect infection in pooled milk samples collected from the aged animals of a dairy farm, which could support TST monitoring and improve bTB control [ 114 ]. In addition, Brahma et al reported a similar sensitivity of PCR targeting CFP-10 protein to that of IGRA and concluded that it may be used as a fast, alternative method for bTB diagnosis from blood samples [ 4 ]. Elsohaby et al reported a difference between the PCR estimates of M. bovis in both blood and milk in dairy cattle, where the sensitivity of PCR conducted on blood and milk samples was 53–95% and 1–60% while its specificity was 95–100% and 43–99% for each sample, respectively [ 72 ].…”
Section: Diagnosis Of Btbmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, early detection of BTB is pivotal to ensure effective control of any outbreak, and minimize the economic impact on farms [7] . The gold standard methods for BTB diagnosis are based on cellular immunity through the intradermal tuberculin skin test (TST) and/or the interferon-gamma release assay (IGRA) [8] .…”
Section: Introductionmentioning
confidence: 99%
“…TST cannot be repeated for at least 60 days because of systemic desensitization caused by the injection of tuberculin. The use of Comparative Intradermal Tuberculin Test (CITT) as a diagnostic test to overcome the problem of false positive reactions of the Single Intradermal test in India is restricted due to unavailability of avian tuberculin (Brahma et al, 2019). In-vitro blood IFN-γ assay measures the cell-mediated immune response of M. bovis infected animals (Reuss, 1995) with the limitation of non-specific responses in a young animal, high logistic demand (culture start is required within 24 hours after blood collection), the requirement of welltrained personnel (Ramos et al, 2015).…”
mentioning
confidence: 99%